Perancangan Sistem Informasi Manajemen Ekstrakurikuler Berbasis Web Pada Sekolah Menengah Pertama 13 Semarang - Hakim, Muhammad Luqmanul; Wahyudi, Eko Nur (STMIK Banjarbaru, 2024)
The extracurricular management and recording system that runs at SMPN 13 Semarang is not yet efficient because they are still trying to use a manual recording system for each extracurricular. This research aims to design a website-based extracurricular management data system that suits the needs of SMP 13 Semarang, and test and evaluate the usability of the system in extracurricular management. System development explores universal stages in the Prototype procedure. The system design uses object-oriented tools, while the implementation uses the Enterprise Architect interface, the PHP programming language with the Laravel framework and mySQL database. Functional features for logging in, registering, editing student information, viewing attendance and documentation online, and management reporting are validated using Blackbox Testing. The test results show that the functional features are valid in their whole.Keywords: Extracurricular Management; Web-based system; Blackbox testingÂ AbstrakSistem pengelolaan serta pencatatan ekstrakulikuler yang berjalan di SMPN 13 Semarang belum efisien sebab masih dicoba memakai sistem pencatatan manual disetiap ekstrakulikuler. Riset ini bertujuan buat merancang sistem data manajemen ekstrakurikuler berbasis website yang cocok dengan kebutuhan SMP 13 Semarang, dan menguji serta mengevaluasi daya guna sistem dalam manajemen ekstrakurikuler. Pengembangan system menjajaki tahapan-tahapan universal dalam tata cara Prototype. Desain sistem memakai tools berorientasi objek, sebaliknya implementasi memakai interface Enterprise Architect bahasa pemrograman PHP dengan framework Laravel serta database mySQL. Fitur- fitur fungsional buat login, pendaftaran, edit informasi siswa, serta memandang absesnsi serta dokumentasi secara online, dan pelaporan manajemen divalidasi memakai Blackbox Testing. Hasil uji menampilkan fitur-fitur fungsional sudah berjalan valid secara keseluruhan.Â